BASE COMPOSITION OF THE DEOXYRIBONUCLEIC ACID OF SULFATE-REDUCING BACTERIA - Sigal, Nicole (1963)
Sigal, Nicole (Laboratoire de Chimie Bactérienne du CNRS, Marseille, France), Jacques C. Senez, Jean Le Gall, and Madeleine Sebald. Base composition of the deoxyribonucleic acid of sulfate-reducing bacteria. J. Bacteriol. 85:1315–1318. 1963—The deoxyribonucleic acid constitution of several strains of sulfate-reducing bacteria has been analytically determined. The results of these studies show that this group of microorganisms includes at least four subgroups characterized by significantly different values of the adenine plus thymine to guanine plus cytosine ratio. The nonsporulated forms with polar flagellation, containing both cytochrome c(3) and desulfoviridin, are divided into two subgroups. One includes the fresh-water, nonhalophilic strains with base ratio from 0.54 to 0.59, and the other includes the halophilic or halotolerant strains with base ratio from 0.74 to 0.77. The sporulated, peritrichous strains without cytochrome and desulfoviridin (“nigrificans” and “orientis”) are distinct from the above two types and differ from each other, having base ratios of 1.20 and 1.43, respectively.